Auditoría operativa al control interno en el área de crédito y cobranza en la cooperativa de ahorro y crédito Mushuc Runa Ltda., en la ciudad de Guaranda en el año 2023 - Ninabanda Landa, Jenny Beatriz (2025)
4 ABSTRACT This research project titled “Operational Audit of Internal Control in the Credit and Collections Area at the Mushuc Runa Savings and Credit Cooperative Ltda. in the City of Guaranda in the Year 2023” aims to conduct an operational audit of internal control in the credit and collections area of the Mushuc Runa Savings and Credit Cooperative Ltda. A mixed methodology was used, combining quantitative and qualitative approaches; the main areas of focus were identifying deficiencies in the credit granting and recovery processes, and evaluating compliance with internal policies and procedures. The results indicate deficiencies in the application of credit policies, incomplete documentation in files, and inefficient processes for portfolio recovery. The recommendations include improving internal control mechanisms, implementing a constant monitoring system, and training staff in credit and collection policies. Conclusion: The research highlights the need to strengthen internal control in the cooperative to reduce delinquency and improve operational efficiency, contributing to the sustainability of the entity and the confidence of its members